Torsion of the Retroperitoneal Kidney: Uncommon or Underreported? - Michael Sosin; Wuya Lumeh; Matthew Cooper (Case Reports in Transplantation)
Vascular torsion in a renal allograft after placement in the retroperitoneum is rare and has only been reported twice in the literature. It is an extrinsically mediated process that occurs at the vascular pedicle resulting in graft compromise and potential loss. Rapid diagnosis and immediate surgical intervention may salvage allograft function. Herein, we present a unique case of a 42-year-old male that developed renal allograft torsion following a second kidney transplant placed in the retroperitoneum. Immediate detorsion did not resolve allograft dysfunction, and a biopsy revealed acute cellular mediated rejection. After antithymocyte globulin treatment, allograft function was salvaged. A review of the current literature shows that the incidence, morbidity, and long term allograft function of intraperitoneal and extraperitoneal torsion are different. As such, torsion of the retroperitoneal kidney demonstrates encouraging allograft salvage rates. Only the third case reported to date, this serves as a contribution to the growing body of literature in retroperitoneal renal torsion and reviews the risks, medication considerations, diagnostic tests, and treatment modalities in a unique disease process.